Implementation of Efficient Energy Policy in Russia: Energy Consumption Monitoring and Problem Analysis - Mukhametshin, Rustam Z.; Kryukova, Nina I.; Beloborodova, Alexandra V.; Grinenko, Aleksandr V.; Popova, Olga V. (International Journal of Energy Economics and Policy, 2019)
The implementation of an efficient energy policy in Russia as an integral part of the social and economic strategy as a whole gives a high profile to the issues of energy consumption monitoring. The importance of the energy sector to the industrial development of all Russian regions requires close attention to the accounting and rational use of energy resources in order to reduce the energy dependence of all industries and make Russian economy less energy-intensive whilst more energy-efficient. The analysis of strategic documents in the field of energy saving proves the importance of the Russian Federation, which is one of the leaders of the world energy sector. The purpose of the article is to study the energy aspects of energy consumption in the regions of the Russian Federation, to conduct their comparative analysis and evaluation, and to identify problems in the supply of energy resources. The methods of research applied to study this problem include data collection and synthesis methods; a balance method; a time-series method; tabular and graphical methods of the study results visualization. The article presents the dynamics of electricity consumption in the regions of the Russian Federation broken down by federal districts and macro-regions set out in the Russian Federation spatial development strategy; also, the consumption balance by types of energy resources is provided for various fuels. In addition, it provides a brief description of the Russian integrated power system operation reflecting the generation and consumption of electricity among the main power systems of the country. Based on the analysis of Russia’s energy development forecast, using scenario approaches, the article concludes that the energy efficiency of the national economy requires improvement and there is a need to implement energy-saving projects. The information contained herein is of practical value for the professionals involved in the analysis and evaluation of energy resources consumption and assessment of their contribution to the national economy. The results of the study reveal fundamental differences in the consumption and use of energy resources throughout Russia’s regions. Keywords: energy resources monitoring, energy consumption, energy security, energy saving, energy strategy. JEL Classifications: D24; Q43; M31 DOI: https://doi.org/10.32479/ijeep.7967